EVALUASI PROGRAM PRAKTIKUM PENEMPATAN KLINIS DALAM PENGEMBANGAN KOMPETENSI PEDAGOGIK CALON GURU PAUD PADA FAKULTAS ILMU PENDIDIKAN UNIVERSITAS XYZ: EVALUATION OF CLINICAL PLACEMENT PRACTICUM PROGRAM IN DEVELOPING PEDAGOGICAL COMPETENCE OF CANDIDATE OF EARLY CHILDHOOD TEACHERS IN FACULTY OF EDUCATION UNIVERSITY XYZ - Sitompul, Estahayati; Priyatna, Novel (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
Pedagogical competence is one of the important competencies for teachers. XYZ University is one of the LPTK to ensure prospective teachers achieving pedagogical competence by organizing the Clinical Placement Practicum program. This research is an evaluation study using the Context Input Process Product (CIPP) model. Data collection was through interviews, questionnaires, and document studies. The data validity was through the process of source triangulation. Data analysis used the stages of data reduction, presentation, and conclusion drawing. The evaluation results: a) Context, it appears that the program's objectives align with the achievement of the faculty’s graduate profile, particularly in the aspect of competence, specifically in pedagogical competence; b) Input, the resources used have not fully supported the effectiveness of the PPK program implementation to support the pedagogical competence of students; c) Process, the DPL and Mentor Teachers have made efforts with various mentoring actions. However, the guidance provided needs to be further improved; d) Product, students are able to provide emotional support, listening and interacting skills, ability to group early childhood children according to developmental aspects, and consistently applying rules and procedures. However, students need to improve the ability to plan appropriate methods and teaching aids, provide scaffolding, reinforce the child's potential, maintain a reflective and evaluative attitude personally, and use appropriate methods and teaching aids.